English vocabulary learning through watching YouTube videos and reading blog posts - Arndt, H (2014)
Research on the Online Informal Learning of English has found that social media can facilitate language learning, mainly in the domain of vocabulary. It does so not only by providing the necessary language input, but also through the unique ways in which social media platforms encourage interaction between the user and the content as well as with other users. The present study investigated English vocabulary acquisition from engagement with two different types of social media: blog posts and video blogs. It also explored how learners make use of the unique opportunities for user-content and user-user interaction offered by these media. For this purpose, screen-captures of participants engaging with the blog posts and videoblogs were collected. The results showed that incidental vocabulary learning occurred, in approximately equal amounts, from reading blog posts and watching video blogs. They also revealed that different types of vocabulary knowledge were gained from the two input modalities. Written input was found to promote greater gains in orthographic knowledge than videos. In turn, the videos promoted greater recognition and recall of the target words' meaning and recall of their grammatical function. The analysis of the screen-captures indicated that learners did not often make use of the unique features offered by the blog and video platforms. The findings are discussed in the wider context of user engagement with social media and virtual communities.